PEMBERDAYAAN IBU PKK MELALUI PELATIHAN PEMBUATAN TOTEBAG ECOPRINT DI KELURAHAN NGAGEL REJO, SURABAYA - Mulyana, Puji Rahmasani; Nisrina Maulida Putri; Fernanda Dwi Ardiyanto; Raihana Sakhi Aswanda; Dita Atasa (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
This community service activity is motivated by the importance of empowering women through developing environmentally friendly, locally-based skills. The PKK women of Ngagel Rejo Village, Surabaya, as community service partners, have great potential in developing ecoprint crafts as a creative and sustainable business. However, limited knowledge and technical skills are the main obstacles in developing these products. The objective of this activity is to improve the understanding, skills, and environmental awareness of PKK members through training in making ecoprint tote bags using the pounding technique. The methods used include preparation, socialization, demonstration, hands-on practice, and pretest and posttest-based evaluation. The results of the activity showed an average increase in participant scores of 36.88 points, reflecting a significant increase in understanding and skills. The evaluation also showed that 100% of participants felt the training provided new insights, and the majority were interested in developing ecoprint as a creative product. This activity not only has a positive impact on strengthening women's capacity but also supports the principles of environmental conservation and household-based business opportunities